2015
DOI: 10.1002/app.42238
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of acid–base polyimides bearing pendant sulfoalkoxy groups for direct methanol fuel cell applications

Abstract: A series of acid-base polyimides with sulfonic acid groups in the side chains have been prepared, based on a new synthesized sulfonated diamine monomer containing pyridine functional group. The effect of the introduction of pyridine groups into copolymer backbone on the properties of membrane were evaluated through the investigation of membrane parameters. The copolymers produced flexible, tough, and transparent membranes by solvent casting method. All the prepared membranes displayed high thermal stability, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…It was reported that the crosslinking could mitigate excess swelling of IEC membranes . The crosslinking could be generally made by acid–base (electrostatic) interactions or covalent bonds . The ionically crosslinked membranes are not very stable particularly at high temperature and humidity due to the relatively weak electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the crosslinking could mitigate excess swelling of IEC membranes . The crosslinking could be generally made by acid–base (electrostatic) interactions or covalent bonds . The ionically crosslinked membranes are not very stable particularly at high temperature and humidity due to the relatively weak electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…As new clean energy supplies for portable and stationary electronic devices, PEFCs and DMFCs have attracted much attention of scientists. PEM is a very important component of PEFCs and DMFCs . The perfluorosulfonic acid copolymer membranes, such as Nafion (Dupont), are the most commonly used PEMs in PEFCs and DMFCs until now .…”
Section: The Effects Of Side Groups On Specific Properties Of Polyimidesmentioning
confidence: 93%
“…PEM is a very important component of PEFCs and DMFCs. 169,170 The perfluorosulfonic acid copolymer membranes, such as Nafion (Dupont), are the most commonly used PEMs in PEFCs and DMFCs until now. 171 However, the high cost and the high methanol permeation limited their wide practical applications.…”
Section: Proton Conductivity and Water Stabilitymentioning
confidence: 99%
“…Unlike PdAS(10) MS, PdAS(10) OS did not show metal particles on the surface or a diffraction pattern in electron diffraction analysis. The XRD analysis in Figure 11 exhibits the typical broad signals associated with the non-crystalline structure of crosslinked polymer matrix at 19 2θ value 60 and a second shoulder around 43 2θ value. Furthermore, for PdAS (10) MS is possible to see the planes of diffraction associated with metallic Pd according to TEM characterization and XPS spectra.…”
Section: As and Pdas Characterizationmentioning
confidence: 99%